Enhancing the Kinetics of Li‐Rich Cathode Materials through the Pinning Effects of Gradient Surface Na+ Doping. Issue 6 (12th December 2015) - Qing, Ren‐Peng; Shi, Ji‐Lei; Xiao, Dong‐Dong; Zhang, Xu‐Dong; Yin, Ya‐Xia; Zhai, Yun‐Bo; Gu, Lin; Guo, Yu‐Guo
Abstract : Gradient surface Na‐ion doping is realized and demonstrated as an effective strategy to enhance the kinetics of Li‐rich cathode materials. Owing to the pinning effect of Na‐doping in the Li layer, the resultant Li‐rich particles exhibit superior electrochemical performances in terms of specific capacity, Coulombic efficiency, and cycling stability.